Cooperative behavior and affect heuristic. When the rationality of love matters - Oliverio, Albertina (Frontiers in Sociology, 2025)
A central problem of social theory consists in explaining individual cooperative behavior. One of the main interpretations is rooted in the rational choice theory, born from the homo oeconomicus model, which proposes instrumental rationality, maximization of expected utility and self-interest as unique presuppositions of individual behavior. These assumptions have been widely criticized, especially concerning their descriptive adequacy in cases of cooperative behavior. Numerous empirical evidence shows how individual behavior can be disinterested in these cases, not based on instrumental calculation and, therefore, explainable on the basis of other dimensions in cognitive human system and individual action. Based on the literature developed in the field of cognitive psychology and experimental economics, the article proposes to analyze cooperative behaviors (conceived in a broad sense since not necessarily implying shared goals), considering components of the rationality of a cognitive and emotional nature, using the concept of affect heuristic. It shows how some emotional behavioral responses (e.g., love, fairness moods, etc.) can be crucial in explaining individual selfless behaviors and their role in developing cooperation. Our analysis is developed in the light of a broader cognitive system and a more extended notion of rationality than the strictly economic one.